A Fatal Case of Takayasu Arteritis Presented with Autoimmune Hemolytic Anemia (Bangladesh Journal of Medicine, 2026)
Takayasu arteritis (TA), a rare granulomatous vasculitis primarily affecting large vessels, presents with a myriad of complex clinical features. This case report discusses a 24-year-old female presenting with fever, breathlessness, and heart failure, ultimately diagnosed with Takayasu arteritis (TA) complicated by autoimmune hemolyticanemia (AIHA). Despite treatment with antibiotics, steroids, and methotrexate, alongside interventions for pneumonia and tuberculosis, the patient’s condition deteriorated, resulting in mortality. The case underscores TA’s diverse and challenging clinical manifestations, including cardiac involvement and AIHA, emphasizing the need for multidisciplinary management and heightened clinical awareness. Despite efforts to address complications, the patient’s outcome highlights the complexity and severity of TA, warranting further research and awareness in clinical practice.Bangladesh J Medicine 2026; 37(1): 72-76